Effectiveness of School Police Officer Engagement in Bullying Prevention and Intervention in Belgrade Secondary Schools - Grmuša, Adrijana (NBP. Nauka, bezbednosti, policija, 2024)
Engagement of school police officers (SPOs) within the Serbian education system is an important element of the school’s cooperation with the environment in bullying prevention and intervention. However, there is a lack of empirical data on the effectiveness of SPO engagement. For this reason, this paper presents the results of a research on the current state of SPO engagement and the perception of the effectiveness of SPO engagement in bullying prevention and intervention by students and members of the Team for protection, conducted in 19 Belgrade secondary schools in the school year 2020/2021. Data on the current state of engagement were collected through observation, while data on perceptions of effectiveness were collected through interviews with 44 members of the Team for protection and a survey of 1,526 students. In terms of bullying prevention, this research has shown that SPO engagement has the potential to be effective by achieving a deterrent effect, but only if SPOs are present at the time when the risk of bullying incidents is highest. In terms of bullying intervention, the results indicate that although SPOs are willing to intervene, their engagement is not effective as only a small number of victims ask them for protection in bullying cases and only in 30% of cases SPO managed to help. The implication of this research refers to the need to improve the interaction between students and SPOs, primarily by strengthening SPOʼs educational role and providing SPOs with adequate training to perform their duties in school.
Keywords: bullying; school police officer; secondary schools; school security